Prevention of Sexual Harassment of Students Through Sex Education Information Services Using Video Media - Indriasih, Ayu; Mudjiran, Mudjiran; Syukur, Yarmis; Sukma, Dina (Universitas Negeri Padang, 2023)
This study aims to examine the effectiveness of sex education information services using video media to prevent sexual harassment of students.The research method used is quantitative research. This type of research is a Quasi Experiment Design with a Pretest Posttest Group Design. The population in this study were 284 students. The research sample was 30 students for the experimental group and 30 students for the control group. Sampling used Cluster Sampling. The research instrument used a Likert Scale model, the data were analyzed using the Wilcoxon Signed Ranks Test and the Kolmogorov-Smirnov with the help of SPSS version 24.00.The results of the study show that; (1) there is a significant difference in students' understanding of sex education to prevent sexual harassment in the experimental group before and after participating in information services using video media, the probability number is below alpha 0.05 (0.003 <0.05), (2) there are differences in understanding sex education of students to prevent sexual harassment in the control group before and after participating in information services without using video media obtained a probability number below alpha 0.05 (0.003 <0.05), (3) there are differences in students' understanding of sex education to prevent sexual harassment in the experimental group given information services using video media with a control group provided information services without using video media obtained by 0.002, or probability below 0.05 (0.002 < 0.05). The difference can be seen from the posttest results of the experimental group which are higher than the posttest results of the control group. The findings of this study can be concluded that sex education information services using video media are more effective in preventing acts of sexual harassment on students.